How to rescue Ontario's Endangered Species Act: a biologist's perspective - Jordanna N. Bergman; Allison D. Binley; Rowan E. Murphy; Caitlyn A. Proctor; Thuong Tran Nguyen; Elise S. Urness; Michelle A. Vala; Jaimie G. Vincent; Lenore Fahrig; Joseph R. Bennett (Canadian Science Publishing, 2020)
owerful and well-implemented legislation is an important step towards the protection and recovery of species at risk of extinction (Ray and Ginsberg 1999; Schwartz 2008). For example, the U.S. Endangered Species Act, despite its flaws, has resulted in several species being saved from extinction (Evans et al. 2016). Although Canada has national legislation to protect species at risk and provide for their recovery (Species at Risk Act (2002), S.C. 2002, c. 29), this legislation generally only applies to lands that are under federal government jurisdiction, with the exception of emergency orders, which are rarely implemented. Since most land in Canada is under provincial jurisdiction, species protection often effectively falls under provincial species-at-risk legislation (Olive and McCune 2017).